Supercritical Carbon Dioxide-Assisted Process In Synthesis of Polymer/Clay Melt - Norazlina, Hashim; Kamal, Yusoh (The Polymer Society of Korea and Springer 2015, 2015)
Nanocomposites are currently being used in a number of fields, and new applications are continuously being developed including mechanical and biomaterial devices, as well as various in solar and fuel cells applications. Generally, the synthesis of polymer nanocomposites are done using solution chemistry, and this may raise serious concerns regarding air and water pollutions. Immediately, the ‘green’ method using supercritical carbon dioxide (scCO2) has grabbed the attention of researchers who are responsible to synthesize polymer composites by non-hazardous routes. Extrusion processes would benefit from the use of scCO2 since the rationale of the extrusion process is to formulate, provide texture and shape molten polymers by forcing them through a die. ScCO2 has been used in several studies as a medium of clay dispersion in polymer matrix by providing a solvent-free fabrication route for nanocomposites. Furthermore, it has more favorable interactions with polymers compared to other inert gases and has the ability to be dissolve in large quantities. It acts as a plasticizer, which modifies viscosity and interfacial properties of the polymer drastically. In this paper, experimental and theoretical studies of solubility and viscosity of several polymer melts in clay are discussed in detail. The assistance of scCO2 in clay dispersion and as a foaming agent has been reviewed extensively